Exploring Patients’ Perceptions of One-step Surgery for Primary Cutaneous Melanoma: A Qualitative Study - Margueritte Lim; Thibault Kervarrec; Youssef Mourtada; Laura Chaput; Jean-Pierre Lebeau; Laurent Machet (Acta Dermato-Venereologica, 2024)
High-frequency ultrasonography (> 20 MHz) has allowed for preoperative measurement of melanoma thickness and thus a one-step surgery strategy. The potential benefits of one-step surgery to patients remain unexplored. From June 2022 to August 2023, 2 dermatologists conducted semi-structured individual interviews with patients who had undergone HFUS examination allowing the choice for one-step surgery (group A) and with patients who had had standard two-step surgery (group B). Analysis of interviews with 21 patients (age range 31–81 years) revealed 5 main themes: (a) understanding the diagnosis, highlighting the significance of clear and comprehensive medical explanations; (b) personal factors considered in treatment decisions, including preferences for minimizing surgical procedures; (c) making choices, bearing responsibility, thus showcasing different levels of patient involvement in decision-making; (d) high- frequency ultrasonography reassurance emphasizing the role of medical reassurance, and (e) patient satisfaction, discussing surgical outcomes and the decision-making process. The majority of participants expressed a clear preference for one-step surgery, perceived as a pragmatic and fast surgical strategy while minimizing interventions. In conclusion, the results emphasize the importance of patient-centred care. These insights can guide improved preoperative consultations and enhance shared decision-making between healthcare professionals and patients regarding melanoma treatment strategies.